2008
DOI: 10.1007/s00455-008-9163-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Displacements During the Swallow in Patients with Early Laryngeal Cancers and Other Early Primary Cancers of the Head and Neck

Abstract: Spatial movement of pharyngeal structures involved in swallowing was assessed by videofluoroscopy in 24 patients with early (T1N0) carcinoma of the larynx prior to curative treatment using an identical radiotherapy regimen (55 Gy in 20 daily fractions), and in 24 patients who had early primary head and neck cancers in other locations that would not be expected to interfere with the pharyngeal swallowing process. There were no significant differences between the laryngeal cancer patients and the other patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, laryngeal penetration can occur in approximately a half of patients with early staged glottic cancer [22], despite other biomechanical measurements being within normal range. Again, we should note that penetration can occur as part of a healthy swallow [19].…”
Section: Swallowing Impairmentmentioning
confidence: 95%
“…However, laryngeal penetration can occur in approximately a half of patients with early staged glottic cancer [22], despite other biomechanical measurements being within normal range. Again, we should note that penetration can occur as part of a healthy swallow [19].…”
Section: Swallowing Impairmentmentioning
confidence: 95%
“…Before treatment, the efficiency of the swallowing function of a patient with head and neck cancer is often preserved. Ford et al [9] did not find any difference in spatial movements between a study population with early laryngeal cancer and normal subjects using videofluoroscopic analysis. In a pretreatment videofluoroscopic study, Pauloski et al [10] noted that patients with head and neck cancer demonstrated highly functional swallowing before treatment with a pharyngeal transit time that did not exceed 1 s. However, 41% of the patients complained of dysphagia, especially those with T3 and T4 lesions, where the pharyngeal transit time was significantly longer and pharyngeal residue was found in more than 70% of the patients.…”
Section: Acoustic-radiological Studymentioning
confidence: 98%
“…Thermoplastics is a mature tool that ensures the relative consistency of a patient’s position during positioning and treatment ( 67 ). However, movement of internal organs during treatment, such as pharyngeal swallowing activity, respiratory movement, gastrointestinal motility and heartbeat, is an important factor affecting the accuracy of radiotherapy ( 68 70 ). Because of the long implementation time of SBRT (minutes to tens of minutes) ( 71 , 72 ), it is unlikely the movement of organs in the body near the target area can be avoided.…”
Section: Radiotherapy Simulationmentioning
confidence: 99%